The police and the public: policing practices and public trust in Latin America - Malone, Mary Fran T. (Policing and society, 2021)
Over the past two decades, most Latin American countries have struggled to create or reform their police forces while simultaneously confronting sharp increases in violent crime. Reformers have gravitated towards community-oriented policing practices, which aim to rely on preventive tactics and build closer ties between police officers and the public. The implementation of such policing practices can be daunting, particularly for countries with authoritarian histories of policing and/or military repression. When confronting rising crime rates, some new democracies are tempted to revert to authoritarian policing practices and circumvent constitutional safeguards on human rights and civil liberties. Still, some countries have resisted such temptations, and seriously invested in community-oriented policing practices. However, do these community-oriented policing practices lead citizens to trust the police more? Or does public trust depend more heavily on results – particularly in countries undergoing crises in public security? To answer these questions, we analyze public trust in the police in 17 Latin American countries through a series of regression analyses of the Latin American Public Opinion Project’s (LAPOP) 2016–2017 survey data. We find that community-oriented policing practices tend to garner more public trust, but that perceptions of police effectiveness are equally important.